1990
DOI: 10.1007/bf01732883
|View full text |Cite
|
Sign up to set email alerts
|

Acquired protein C and S deficiency, inflammatory bowel disease and cerebral arterial thrombosis

Abstract: Thromboembolic complications may occur in inflammatory bowel disease. Recently, we had the opportunity to observe a case of a cerebral arterial thrombosis in a young patient with active ulcerative colitis. Investigation of blood coagulation revealed a temporary Protein C, Protein S and Factor II deficiency. To our knowledge, this is the first reported case of a temporary Protein C and S deficiency in a patient with thrombosis and inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 20 publications
1
24
0
3
Order By: Relevance
“…Our results revealed that factor IXa, Xa, Va, VIIIa and AT-III levels were higher in active UC and IC than inactive UC, and suggested that common pathways were initiated by extrinsic and intrinsic pathways. (2,17,26). On the other hand, the present results suggested that there were no cases of hereditary thrombophilia in our study, since AT-III, protein C and protein S were within the normal range among all patients.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Our results revealed that factor IXa, Xa, Va, VIIIa and AT-III levels were higher in active UC and IC than inactive UC, and suggested that common pathways were initiated by extrinsic and intrinsic pathways. (2,17,26). On the other hand, the present results suggested that there were no cases of hereditary thrombophilia in our study, since AT-III, protein C and protein S were within the normal range among all patients.…”
Section: Discussionsupporting
confidence: 43%
“…Normalization of markers of the coagulation system has been documented during treatment, which suggests that the observed abnormalities are secondary to the disease state (5,13). There have been no complete studies on the hypercoagulable state in UC on the total coagulation system, although there have been many reports on a part of the system (1)(2)(3)(4)(5)(6)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Therefore, the first aim of this study was to compare active with inactive UC in relation to the hypercoagulable tendency in the total coagulation system.…”
Section: In Patients With Inflammatory Bowel Disease (Ibd) Mucosal Amentioning
confidence: 99%
“…Deficiency of the proteins C and S in IBD patients was proposed by the studies of Jorens et al [38] gree of inflammatory activity and prothrombotic abnormalities has been found [19]. Studies using sensitive and Aadland et al [39,40].…”
Section: Hypercoagulability In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Cerebral arterial thrombosis was reported after acquired protein S deficiency related to nephrotic syndrome [22] and inflammatory bowel disease [23], Acquired free pro tein S deficiency by using oral contraceptives is controver sial [25][26][27][28], A high prevalence of free protein S deficiency was found in hospitalized patients over 60 years of age, even in the absence of a predisposing condition [7]; our control and patient groups were composed o f younger subjects and no case of free protein S deficiency was found in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%